Piezoelectricity Organic and Inorganic Materials and Applications - Vassiliadis, Savvas G.; Matsouka, Dimitroula (IntechOpen, 2018)
Scientifically defined in 1880 by the Curie brothers, piezoelectricity - from the Greek piezein, meaning to press (squeeze), and ilektron, meaning amber, a material with electrostatic properties - is a phenomenon with many applications. The related piezoelectric materials have been undergoing a long-lasting evolution over the years until today. The field of organic and inorganic piezoelectric materials is continuously expanding in terms of new substances used, new structures, and new applications. The seven chapters of this book present modern aspects and technological advances in the field of piezoelectric materials and applications. To present a balanced view of the field, some chapters focus on new piezoelectric materials and structures, while others examine interesting applications of piezoelectric sensors, energy harvesters, and actuators.